PELAKSANAAN PEMBERIAN BANTUAN HUKUM KEPADA MASYARAKAT MISKIN DI YAYASAN LEMBAGA BANTUAN HUKUM LEMBAGA PENGAWASAN KEBIJAKAN PEMERINTAH DAN KEADILAN (YLBH LP-KPK) - Andi Nurhidayah; Amirul Suriatno Piola (Fakultas Hukum Universitas Borobudur, 2025)
The government has issued Law Number 11 of 2016 concerning Legal Aid, but to date, many poor people have not been reached and have not received maximum benefits from legal aid provided by legal aid institutions. This study discusses the implementation of legal aid provision to the poor at the YLBH LP-KPK and the obstacles faced in providing such legal aid. This study uses an empirical normative juridical research method. The results show that the implementation of legal aid provision to the poor at YLBH LP-KPK begins with the application and examination stage of the legal aid application, acceptance or rejection of the legal aid application, and the provision of legal aid through litigation and non-litigation. The implementation of the legal aid provision is in accordance with the provisions of Articles 2 to 17 of Law Number 16 of 2011 concerning Legal Aid. Obstacles faced in providing legal aid to the poor include not having an identity card, not understanding the law, not being able to read and write, and when submitting a legal aid application, it turns out that they have given power of attorney to another legal aid institution or advocate.